(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2022)
Advertising in the digital age has been playing a very important role when positioning a product or services is concerned, achieving customer loyalty in companies requires disruptive strategies through the use of technologies to bring the message of the most direct advertising to the interested party. This article seeks to show features of a web system and an APP, to manage advertising through the interaction of people with an intelligent recycling caneca supported by the Internet of Things (Tascón, M., 2020), in that system it was possible to implement an artificial intelligence algorithm under the K- Means technique (Nuin et al., 2020), which seeks to analyze the behavior of people’s tastes in a shopping center. Three-phase research was developed, the first allowed a state of the art to be carried out on different artificial intelligence techniques used for the analysis of people’s behaviors, the second Phase was the analysis of functional and non- functional requirements of the web system and the APP, supported under the agile web engineering development methodology (iWeb) (Ramiro, 2018) and the third Phase the development of interfaces and coding of the different modules of the system. In the end it was possible to obtain a system that allows the partners of the shopping center to upload advertising which will be seen by customers who interact with the recycling caneca showing you the advertising of interest according to their purchase profile.